International Comparative Educational Research in Latvia: Current Results and Trends - Geske, Andrejs; Grinfelds, Andris; Kangro, Andris (Acta Paedagogica Vilnensia, 2003)
The article presents results of the comparative educational research in Latvia in latter ten years. The article reviews JEM TIMSS and SITES, OECD PISA research results gained in Latvia and other countries. This research material helps to form a view on Latvian and other countries educational research.